INDENTIFICATION OF STUDENTS LEARNING DIFFICULTIES IN LEARNING IN THE HIGH GRADES OF SDN 2 TOLAI - Ni Kadek Sri Mertasari; I Made Nuhari Anta; Ni Made Mega Hariani (JATMIKA : Journal Education and Learning of Elementary School, 2023)
This study aims to determine student learning difficulties and the causal factors so that there are efforts made by teachers and parents. The design used in this study is descriptive qualitative. The results of this study indicate that the difficulties experienced by high grade students are in the learning disability category of dyslexia, slow learner learning difficulties, pra-academic learning difficulties in the category of cognitive learning difficulties. The difficulties experienced by students in learning are caused by internal factors, namely: learning motivation, interest in learning, and talent, then external factors, namely: the community environment, family environment and massa media, so that the efforts made by the teacher are: using smart books to read, repeating material or remedial, giving advice and motivation to learn, assessing student achievement, and creating a conducive classroom atmosphere, then the efforts made by parents are: giving advice, accompanying when learning and providing facilities.